The Role of the Indonesian Food and Drug Authority (Badan Pengawas Obat dan Makanan-BPOM) in Skincare Overclaim Cases: Consumer Protection Perspective Due to Negligence in Monitoring Inconsistencies in Product Content and Labeling - Aprilianti, Prashandya Natasya Putri; Toteles, Aris; Evi, Evi (Journal of Law, Politic and Humanities, 2025)
The skincare industry in Indonesia is experiencing rapid growth but is accompanied by an increase in cases of overclaim, namely excessive or inconsistent claims between the content and product labels circulating on the market. This practice not only misleads consumers but also has the potential to pose serious health risks. This study aims to analyze the role of the Indonesian Indonesian Food and Drug Authority in cases of skincare overclaim from a consumer protection perspective, especially due to negligence in supervising the inconsistency of product content and labels. The research method used is normative juridical with a statutory approach, reviewing laws and regulations such as Law Number 8 of 1999 concerning Consumer Protection, Law Number 17 of 2023 concerning Health, and the Regulation of the Indonesian Food and Drug Authority. The results of the study show that BPOM has a role in pre-market and post-market supervision of skincare products. However, there are still gaps in the supervision system that cause products with inconsistency in claims to continue to circulate and harm consumers. This study recommends strengthening the supervision and law enforcement mechanisms for business actors and the Indonesian Food and Drug Authority in order to ensure more effective consumer protection and prevent similar cases from recurring in the future